ANALISIS PROFIL PETANI KELAPA (Cocos nucifera) DALAM SISTEM PRODUKSI DI KECAMATAN MABA TENGAH KABUPATEN HALMAHERA TIMU) COCONUT (Cocos nucifera) FARMERS PROFILE ANALYSIS IN THE PRODUCTION SYSTEM IN MABA TENGAH DISTRICT, EAST HALMAHERA REGENCY - Tulus P J Sihombing; Rima Melati; Suryati Tjokrodiningrat; Natal Basuki; Yusri Sapsuha; Hamidin Rasulu (Jurnal Pertanian Khairun, 2025)
Coconut farming is a dominant agricultural activity in Maba Tengah District and serves as the main source of livelihood for the local community. Understanding farmers’ profiles is essential for assessing their capacity within the coconut production system. This study aims to analyze the profile of coconut farmers and its relevance to the coconut production system in Maba Tengah District, East Halmahera Regency. The research was conducted using survey and interview methods, with purposive sampling involving 20 coconut farmers. Data were collected through structured questionnaires and analyzed using quantitative descriptive analysis. The results show that coconut farmers are predominantly male and fall within productive age groups (31–59 years). Most farmers have junior or senior high school education levels, with cultivation areas ranging from 30,000 to more than 50,000 m². Average production per harvest varies between 750 kg and 1,250 kg, while annual income ranges from Rp 20,000,000 to Rp 80,000,000. Coconut farming is more commonly practiced by the Maba ethnic group than by Javanese farmers. These farmer characteristics reflect the human capital capacity that supports the effectiveness of the coconut production system and provides a foundation for the future development of coconut-based agrotechnology in East Halmahera.